2002
DOI: 10.1002/jmv.10242
|View full text |Cite
|
Sign up to set email alerts
|

Low hepatitis B prevalence among pre‐school children in Denmark: Saliva anti‐HBc screening in day care centres

Abstract: Although Denmark has a low hepatitis B virus (HBV) prevalence, HBV transmission has been reported in Danish day-care centres. The aim of this study was to validate saliva anti-HBc testing as a method for HBV screening, the applicability of saliva sampling to pre-school children, and to determine the HBV prevalence in Danish day-care centres with a high proportion of immigrants. For validation, paired saliva and plasma samples were obtained from blood donors and injecting drug users. Employees and children in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 23 publications
2
7
0
2
Order By: Relevance
“…It is important to note that the oral fluid anti-HBc assay had high sensitivity in individuals presenting active infection compared to those with anti-HBc isolate and past HBV infection. This is in agreement with prior observations of the best HBV assay performance using oral fluid samples from ambulatory settings [31] and among those with active infection with 90.5% sensitivity when only HBV infected individuals were included in the study [9].…”
Section: Discussionsupporting
confidence: 92%
“…It is important to note that the oral fluid anti-HBc assay had high sensitivity in individuals presenting active infection compared to those with anti-HBc isolate and past HBV infection. This is in agreement with prior observations of the best HBV assay performance using oral fluid samples from ambulatory settings [31] and among those with active infection with 90.5% sensitivity when only HBV infected individuals were included in the study [9].…”
Section: Discussionsupporting
confidence: 92%
“…The study also failed to show evidence of transmission of hepatitis B from immigrant schoolchildren to Danish-born schoolchildren. Another Danish study identified only one child (an immigrant from Somalia) with resolved infection in 585 preschool children where 55 % were immigrants [36]. A study from Australia showed a low prevalence of HBV infection in low-risk schoolchildren irrespective of the proportion of high-risk children in their classes [37].…”
Section: Discussionmentioning
confidence: 99%
“…Transmission through saliva, though unlikely, is certainly possible, especially where the boy shows a high HBV viremia [1]. The risk of transmission in day care is low, but has been reported and confirmed by genotyping [2][3][4][5][6]. The theoretical routes of transmission are direct through small wounds and, more important, by child bites.…”
mentioning
confidence: 99%